Effects of metformin+sitagliptin versus metformin + glibenclamide combinations on lipid profile, body mass index and kidney function in Iraqi patients with type 2 diabetes mellitus. - Abbas Al-Temimi, Hassan Mohammed; Al-Shamma, Kassim; AlRubaie, Salim (Al Mustansiriyah Journal of Pharmaceutical Sciences, 2013)
Until 1995, only two options for pharmacologic treatment were available for patients with diabetes; sulfonylurea (for type 2 DM only) and insulin (for type 1 or 2). Since 1995, a number of new oral agents, injectables, and insulins have been introduced in therapy. Currently, six classes of oral agents are approved for the treatment of type 2 diabetes: , sulfonylurea, α-glucosidase inhibitors, biguanides, meglitinides, thiazolidinediones or glitazones& dipeptidyl peptidase-4 inhibitors. This study aimed to evaluate the lipid profile, kidney function and BMI by using two combinations of drugs metformin + glibenclamide and metformin + sitagliptin on patients with T2DM. Sixty eight T2DM patients (and categorized in to two treatment groups) and 34 normal healthy individuals as control group were enrolled in this study group 1 (34 patients ) received metformin 500 mg three times daily + glibenclamide 5 mg twice daily and group 2 (34 patients) received metformin 500 mg three times daily + sitagliptin 100 mg once daily. From each patients 10 ml of blood was obtained by veinpuncture and the serum was separated and used for estimating the lipid profile, kidney function (blood urea and serum creatinin). The mean calculated serum total cholesterol(TC), serum triglyceride(TG), low density lipoprotein cholesterol (LDLc)and very low density lipoprotein cholesterol(VLDLc) were significantly(p<0.05) lower for group 2 patients after 3 & 6 months of treatment (225.88 ± 6.62 mg/dl,214.32 mg/dl ± 4.86 and 197.61 mg/ dl ± 3.4), (252.08±9.07mg/dl, 234.02 mg/dl ± 6.44 and 196.0 mg/dl ± 5.70 ), (96.2± 2.03mg/dl, 94.26 mg/dl ± 2.58, 88.17 mg/dl ± 1.79) and (78.38±3.65mg/dl, 68.50 mg/dl ± 2.9, 60.52 mg/dl ± 2.26)respectively as compared to group 1 (245.7 ± 2.87,235.61mg/dl ± 2.64, 224.9 mg/dl ±2.98 ), (257.38 ± 9.25,249.67 mg/dl ± 8.19 , 235.7 mg/dl ± 7.83 ), (103.14 ± 2.19, 95.64 mg/dl ± 1.19 , 91.64 mg/dl ± 1.196) and (94.74 mg/dl ± 2.93 , 83.79 mg/dl ± 3.28 ) respectively. The picture was different for high density lipoprotein (HDLc) where, significantly (p<0.05) increased for group 2 patients after 3&6 months of treatment (48.37± 1.07, 49.9 mg/dl ± 1.16 and 51.14 mg/dl ± 1.35 ) compared to group 1 patients (43.02±1.24, 44.67 mg/dl ± 1.28 , 46.52 mg /dl ± 1.22). The mean calculated body mass index (BMI) was significantly (p<0.05) lower for group 2 patients after 1&6 months of treatment (26.7 ± 0.35 and 25.3 ± 0.35) than in group 1 patients (28.5 ± 0.55 and 26.95 ± 0.43. This study also showed significantly(p<0.05) lower mean serum blood urea and serum creatinine level for group 2 patients after 3&6 months of treatment (42.9 ± 1.30 , 44.0 ± 1.48 and 44.0 ± 1.59 mg /dl ),( 0.89 ± 0.03 , 0.91 ± 0.03 and 0.98 ± 0.05 mg/dl) respectively compared to that of group 1(60.0 ± 4.25 , 63.0 ± 4.4 and 64.0 ± 4.34 mg/dl), (1.23 ± 0.54 , 1.26 ± 0.55 and 1.32 ± 0.54 mg/dl) respectively. IN conclusion, the combination of metformin + sitagliptin improved lipid profile, kidney function and body mass index more than metformin +glibenclamide combination.